Optimalisasi Sumber Daya Manusia dalam Pengelolaan Kawasan Daerah Aliran Sungai Serayu Berbasis Konservasi - Ahdi, Muhamad; Fauzi, Ahmad (IAI Nasional Laa Roiba Bogor, 2024)
Environmental problems have not been fully addressed. These issues continue to grow in number and variety. In reality, humans should not exploit natural resources excessively as this can cause damage and depletion. Therefore, humans need to be active in managing and preserving the environment. This article aims to understand the support provided in efforts to optimize human resources based on conservation. The methods used include situational analysis (planning), training, evaluation, and ongoing support. The activities carried out show that the mobilized activity pattern in the form of conservation field schools as a training ground has successfully increased the optimization of human resources. Through new experiences and understanding, good land management with a conservation concept can be applied. Conservation of vegetation and technical civil as a result of its activities. This support was carried out in the village of Mlandi, Garung District, Wonosobo Regency, and has successfully reduced soil degradation, landslides, and floods. Community participation has also increased, providing motivation to play an active role and increase awareness and concern for the environment, as well as impacting economic improvement through coffee production.